2012
DOI: 10.1089/aid.2011.0140
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Case–Control Study of Dynamic Changes in Peripheral Blood Th17/Treg Cell Balance and Interleukin-17 Levels in Highly Active Antiretroviral-Treated HIV Type 1/AIDS Patients

Abstract: Our objective was to dynamically observe changes in peripheral blood Th17, Treg cells, and interleukin (IL)-17 levels in HIV-1/AIDS patients before and after highly active antiretroviral therapy (HAART). The study design consisted of a randomized case-controlled study. A total of 33 HIV-1/AIDS patients were chosen to receive a HAART regimen and 30 healthy volunteers were assigned as controls. Peripheral blood Th17 and Treg cells were measured by flow cytometry before or 6 and 12 months after HAART therapy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…27 After staphylococcal enterotoxin B stimulation, PBMCs from HIV-infected patients showed a normal capacity for intracellular production of IL-17/IL-22 (see Fig E4, B and C, in this article's Online Repository at www.jacionline.org), which was in accordance with previous reports that long-term ART induces normalization of the capacity of T cells to produce IL-17/IL-22. 28,29 More importantly, in the absence of any stimulation, the percentages of IL-17-or IL-22-producing PBMCs were significantly higher in HIV-infected patients than in HCs (Fig 5, B and C). The phenotypic analysis showed that these circulating IL-17 1 and IL-22 1 cells were mainly T helper cells (CD3 1 CD4 1 ; see Fig E4, D).…”
Section: Specific Cytokine Environment In Hiv-infected Patientsmentioning
confidence: 88%
“…27 After staphylococcal enterotoxin B stimulation, PBMCs from HIV-infected patients showed a normal capacity for intracellular production of IL-17/IL-22 (see Fig E4, B and C, in this article's Online Repository at www.jacionline.org), which was in accordance with previous reports that long-term ART induces normalization of the capacity of T cells to produce IL-17/IL-22. 28,29 More importantly, in the absence of any stimulation, the percentages of IL-17-or IL-22-producing PBMCs were significantly higher in HIV-infected patients than in HCs (Fig 5, B and C). The phenotypic analysis showed that these circulating IL-17 1 and IL-22 1 cells were mainly T helper cells (CD3 1 CD4 1 ; see Fig E4, D).…”
Section: Specific Cytokine Environment In Hiv-infected Patientsmentioning
confidence: 88%
“…[15][16][17] Therefore, we determined the ratios of Th1:Treg, Treg:Th17, and Th1:Th17 of gut-homing CD4 1 T cells in AHIs. Acute HIV-1 infection led to a loss of guthoming Th1:Treg compared to HCs (Figure 6b), and the Treg:Th17 ratio increased in the gut-homing CD4 1 T-cell subset with statistical significance (Figure 6c).…”
Section: Imbalance Of Gut-homing Th1:treg and Treg:th17 Ratios In Acumentioning
confidence: 99%
“…[10][11][12][13][14] Alterations in Th17:Th1 and Th17:Treg balance also contribute to disease progression in HIV/SIV infection. [15][16][17] The gut-homing receptor integrin a4b7 mediates lymphocyte migration from the circulation to the intestine through interaction with MAdCAM-1 on endothelial cells of gut tissues. 18,19 The binding of integrin a4b7 and HIV-1 gp120 facilitates selective infection and replication in a4b7 CD4 1 T cells, which results in HIV-1 cell-to-cell spreading.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute counts (cells/ll) of lymphocytes in erythrocyte lysed whole blood were determined by FACS Calibur flow cytometry as previously described. 7 The monoclonal antibodies including PE-CD4, PE-CD8, FITC-CD45RA, FITC-CD45RO, APC-62L, PerCP-CD38, and APC-CD25 were purchased from BD Corporation (USA).…”
Section: Facs Analysis Of T Cell Subsetsmentioning
confidence: 99%